Effects of morning vs. evening teriparatide injection on bone mineral density and bone turnover markers in postmenopausal osteoporosis - Michalska, D; Luchavova, M; Zikan, V; Raska, I; Kubena, A A; Stepan, J J (Osteoporosis international, 2012)
UNLABELLED: A 12-month morning teriparatide (TPTD) administration resulted in a larger increase in the lumbar spine bone mineral density (BMD) than the evening application. The results indicate that the response of bone cells to teriparatide treatment depends on dosing time. INTRODUCTION: The aim of this study was to assess the long-term effects of the morning vs. the evening teriparatide administration on BMD and bone turnover markers (BTMs) in postmenopausal osteoporosis. METHODS: Fifty women with established postmenopausal osteoporosis were randomized to 12-month treatment with 20 μg of TPTD, administered daily in the morning or in the evening. The BMD and serum concentrations of C-terminal telopeptide of type I collagen, N-terminal propeptide of type I procollagen (PINP), and tartrate-resistant acid phosphatase isoform 5b (TRAP 5b) were measured at baseline, after 6 and 12 months. General linear model-repeated measurements were used to analyze the data. RESULTS: After 12 months, the lumbar spine BMD grew markedly (p < 0.001) with a significantly greater increase in the morning arm compared to the evening arm (9.1% vs. 4.8%, respectively, p < 0.05). The BMD at the distal radius significantly decreased (p < 0.001), with no differences between the arms. The BMD at proximal femur did not change significantly. After 6 months, the BTMs were significantly increased compared with baseline (p < 0.001). The increases in the evening arm vs. the morning arm, however, were more pronounced in PINP (+358% vs. +215%, respectively) and in TRAP 5b (+70% vs. +37%, respectively) (both p < 0.05). CONCLUSION: 12-month morning administration of TPTD resulted in a larger increase in the lumbar spine BMD than the evening application. The timing of TPTD administration may be important for its efficacy.
Keywords: senioři; teriparatid; Procollagen; senioři nad 80 let; bederní obratle; inhibitory kostní resorpce; vápník; Middle Aged; Drug Administration Schedule; Collagen Type I; Injections, Subcutaneous; kolagen typu I; kyselá fosfatasa; Bone Density Conservation Agents; Peptide Fragments; Calcium; Aged, 80 and over; Peptides; Isoenzymes; ženské pohlaví; Humans; biologické markery; peptidové fragmenty; izoenzymy; Bone Density; postmenopauzální osteoporóza; lidé středního věku; kostní denzita; Phosphates; rozvrh dávkování léků; Acid Phosphatase; peptidy; Teriparatide; prokolagen; Tartrate-Resistant Acid Phosphatase; fosfáty; Biomarkers; injekce subkutánní; Female; Aged; Lumbar Vertebrae; Osteoporosis, Postmenopausal; kyselá fosfatasa rezistentní k tartarátu; lidé